Investigating Code-switching in Teacher Talk in Turkish as a Foreign Language Classrooms - Karaca Turhan, Fatma; Bas, Bayram; Turhan, Osman (HACETTEPE UNIV, 2021)
Teaching Turkish as a foreign language (TFL) has recently gained popularity because of various reasons such 14.05.2020 as migration, education, etc. Studies investigating Turkish offer a different perspective to foreign language teaching. This study sets out to investigate code-switching functions of teacher talk in TFL classrooms and to Accepted: compare in-class practices with teachers' perceptions. Within the scope of the study, English as the code 10.08.2020 switched language was investigated. Data were collected by using semi-structured observation, audio recording, transcription of recordings, and by interviewing four teachers. Findings of this study showed that Online First: introducing a lexical item was the most frequently used function, followed by confirming, answering a 02.09.2020 question, giving instructions. The findings indicated that teachers code-switched to English mostly for educational purposes, and partly for conversational purposes. Educational purposes were mostly observed at Published: word level, whereas conversational code-switching was mainly exemplified at sentence level. Finally, the 31.10.2021 findings showed that classroom practices and teacher perceptions mostly aligned with one another. Teachers regarded English as an ally for TFL teaching at certain points on condition that it is kept at minimum level.
Keywords: Code-switching; functions of code-switching; teacher talk; teaching Turkish as a foreign language; teacher perceptions; ENGLISH; Education & Educational Research